Ultrastructural localization of the fibrinogen-binding domain of streptococcal M protein. - Rýc, M (1989)
Binding of fibrinogen to the M protein located on the surface fibrillae of group A streptococci impedes deposition of complement and thus contributes to the virulence of these organisms. We investigated this binding by electron microscopy using postembedding immunogold labeling. Both fibrinogen and its D fragment formed a distinct dense layer in the surface fibrillae, separated by 10 nm from the compact part of the cell wall. Labeling the sections with anti-fibrinogen or anti-fragment D showed that the fibrinogen-binding region lay within a 25-nm segment of the fibrillae beginning approximately 30 nm from the inner surface of the cell wall. The outer surface of the fibrinogen layer could be labeled with antibody to the amino-terminal half of type 24 M protein, indicating that the fibrillar tips remained exposed after fibrinogen binding. The degree of labeling with anti-fibrinogen, determined by gold particle counting, was the same whether the bacterial cells had been incubated with purified fibrinogen or whole plasma. These results indicate that the fibrinogen-binding region lies in the distal (amino-terminal) half of the M protein molecule but excludes the most distal portion, which is the site of epitopes that interact with opsonic anti-M antibody, and that plasma proteins other than fibrinogen, a number of which are known to bind to group A streptococci, do not interfere with fibrinogen binding.